Field Trial of Cluster Target Detection by Broadband Microwave Photonic MIMO Radar - Yuewen Zhou; Fangzheng Zhang; Jiayuan Kong; Yihan Wang; Jinhu Li; Kunyang Chen; Guanqun Sun; Yuhui He; Shilong Pan (IEEE Journal of Microwaves)
Cluster target detection is challenging for traditional narrow-band radars. Microwave photonic multiple-input-multiple-output (MIMO) radar is an emerging technique for accurate cluster target detection, which enhances range and angular resolution via its large bandwidth and virtual aperture. Previous research on microwave photonic MIMO radars focuses on the effectiveness of photonics-based hardware, while its advantages for practical applications have not been effectively validated. This paper demonstrates a field trial of cluster target detection by a broadband microwave photonic MIMO radar having an 8×8 MIMO array and a bandwidth of 8 GHz per channel. Using a broadband digital beamforming algorithm that compensates for aperture fill time, precise target detection is achieved without beam squint and broadening problems. Meanwhile, grating lobes due to sparse array are well suppressed, which enables the improvement of angular resolution by using large-aperture sparse array. In the experiment, detections of a single drone and three densely distributed drones as a cluster are implemented respectively. By comparing the results of 50-MHz narrowband MIMO detection and 8-GHz full-band MIMO detection, the advantage of broadband microwave photonic MIMO radar is verified. For single drone detection, the range resolution and angular resolution are estimated to be 2.1 cm and 0.17°, respectively, and the grating lobes are well suppressed with peak-to-maximum grating-lobe ratio over 13.5 dB. When detecting three drones as a cluster, the individuals are precisely distinguished and located. The results validate that the microwave photonic MIMO radar has high-resolution detection capability superior to traditional narrow-band radars, and it provides an effective and practical solution for cluster target detection.